Relationship between degenerative medial meniscus lesions and the medial fat tissue thickness of the knee - Eralp Kacmaz, Ismail; Uzakgider, Meliksah; Doruk Basa, Can; Zhamilov, Vadym; Er, Ali; Reisoglu, Ali (Annals of Medical Research, 2021)
Aim: It was aimed to investigate the relationship between fatty tissue thickness in the medial of the knee and degenerative meniscus lesion.Materials and Methods: Images of 300 patients (151 females and 149 males) who had previously taken knee magnetic resonance imaging (MRI) were evaluated retrospectively. The relationship between medial meniscus degenerative lesion (MMDL) and age, sex, side, height, weight, body mass index (BMI), medial fat thickness (MFT), length of medial tibial plateau (MTP) was investigated.Results: Mean age of 300 patients (144 rights, 156 left knees) was 41.4 ± 11.8 (range 18–67) years and 200 of them had degenerative meniscus lesions, 100 of them were not detected.Age, weight, height, BMI, MFT, MTP, and MFT/MTP were all correlated with the presence of an MMDL, and the strongest relationship was with age (p0.001). No significant relationship between weight and MMDL was found. However, both MFT and the MFT/MTP ratio were more strongly correlated with the presence of an MMDL. Logistic regression analysis indicated that the presence of an MMDL was 25 times more likely in patients with a high MFT/MTP ratio (odds ratio, 0.040).Conclusion: In this study, the MFT / MTP ratio was found higher in patients with medial meniscus degenerative lesions than in the healthy population. This study shows that fatty tissue thickness in the medial of the knee can be effective in the formation of degenerative meniscus lesions, as well as BMI. However, this study may form the basis for prospective studies in which factors such as daily activity, profession and sports level are also investigated to create a clearer judgment.
Keywords: Adipose tissue; body mass index; meniscus; meniscus lesion; risk factors